2005
DOI: 10.2337/diabetes.54.2.534
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin and Future Coronary Heart Disease Events Among Men With Type 2 Diabetes

Abstract: Adiponectin, predominantly synthesized in the adipose tissue, seems to have substantial anti-inflammatory properties and to be a major modulator of insulin resistance and dyslipidemia, mechanisms that are associated with an increased atherosclerotic risk in diabetic patients. However, it is unknown whether higher levels of adiponectin are associated with a reduced risk for coronary heart disease (CHD) among diabetic individuals. We investigated the association between plasma adiponectin levels and incidence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
223
3
12

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 336 publications
(250 citation statements)
references
References 50 publications
12
223
3
12
Order By: Relevance
“…Furthermore, adiponectin values may have good prognostic value in terms of CVD. High levels of adiponectin were associated with a decreased risk of CAD in male diabetic patients [47] and with cardiovascular outcomes in patients with end-stage renal failure [48]. A prospective study showed that high plasma adiponectin levels were associated with a lower risk of myocardial infarction in healthy men, independent of CRP level or glycemic status [49].…”
Section: The Role Of Adiponectin In Metabolic Syndrome and Cardiometamentioning
confidence: 99%
“…Furthermore, adiponectin values may have good prognostic value in terms of CVD. High levels of adiponectin were associated with a decreased risk of CAD in male diabetic patients [47] and with cardiovascular outcomes in patients with end-stage renal failure [48]. A prospective study showed that high plasma adiponectin levels were associated with a lower risk of myocardial infarction in healthy men, independent of CRP level or glycemic status [49].…”
Section: The Role Of Adiponectin In Metabolic Syndrome and Cardiometamentioning
confidence: 99%
“…Taken together, the abnormal pro-inflammatory state leads to a worsening of metabolic control, abnormal vascular function and eventually cardiovascular and renal diseases. 7,12 Nebivolol is a highly cardioselective vasodilatory beta 1 receptor blocker, and it has recently been approved in the United States for the treatment of hypertension. 23,24 It lowers blood pressure by reducing peripheral vascular resistance, and significantly increases stroke volume with preservation of cardiac output.…”
Section: Discussionmentioning
confidence: 99%
“…10 Adiponectin levels are inversely correlated with visceral obesity, insulin resistance and hyperlipidemia 11 and increased markers of adiponectin have been associated with a decreased risk in coronary heart disease in diabetic men. 12 In endothelial cells adiponectin decreases VCAM-1 expression and NFkB. 13 Leptin is an adipocyte-specific hormone, which has a central role in regulation of body weight.…”
Section: Introductionmentioning
confidence: 99%
“…High plasma adiponectin levels are associated with a lower risk of myocardial infarction in men (71), a reduced coronary heart disease risk in patients with diabetes mellitus (72), and a lower risk of acute coronary syndrome (73) and, significantly, plasma adiponectin levels rapidly decline following acute myocardial infarction (74).…”
Section: Adiponectinmentioning
confidence: 99%